110 Patient-Specific Cerebral Regional Blood Flow Model Using Quantitative Magnetic Resonance Angiography to Predict Stump Pressure. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Li, Daniel; Zhao, Meide; Amin-Hanjani, Sepideh; Kufahl, Robert; Du, Xinjian; Aletich, Victor A; Alaraj, Ali; Li, Jianmin; Charbel, Fady T
Abstract: INTRODUCTION: Stump pressure (SP) plays an important role in clinical decision-making and surgical management relating to planned cerebral vessel occlusion. The goal of this work is to propose a new patient-specific, regional cerebral blood flow model to predict SP noninvasively. METHODS: A new patient-specific cerebral regional blood flow model using quantitative magnetic resonance angiography (qMRA) was developed to predict the SPs for patients undergoing balloon test occlusion (BTO). This new model is a 1-dimensional regional flow model at patient baseline and with internal carotid artery (ICA) occlusion. The baseline model involves calculating the regional blood flows by vessel flow measurements from qMRA, and utilizing peripheral regional resistances. The regional flow model based on ICA occlusion computes the new blood flows and pressures using the simulated occlusion of the ICA while keeping all peripheral regional resistances the same baseline. SPs calculated using the regional flow model with ICA occlusion were compared against the actual SP measurements during BTOs. RESULTS: The proposed model was applied to 4 patients with ICA aneurysms, 2 of whom passed and 2 of whom failed BTO. The predicted SP using aortic pressure measurement resulted in –5%, –11%, 3%, and 7% error when compared to clinical measurements. The predicted SP using cuff pressure resulted in –6%, –14%, 2%, and 6% error when compared to clinical measurements. CONCLUSION: The proposed model using qMRA data and cuff pressure can be used to predict SP with acceptable error for patients who have undergone BTO.